L-4, a Well-Tolerated and Orally Active Inhibitor of Hedgehog Pathway, Exhibited Potent Anti-tumor Effects Against Medulloblastoma in vitro and in vivo - Zhu, Mingfei; Wang, Hong; Wang, Chenglin; Fang, Yanfen; Zhu, Tong; Zhao, Weili; Dong, Xiaochun; Zhang, Xiongwen (Frontiers in Pharmacology, 2019)
Inhibition of aberrant Hedgehog (Hh) pathway had been proved to be a promising therapeutic intervention in cancers like basal cell carcinoma (BCC), medulloblastoma (MB) and so on. Two drugs (Vismodegib, Sonidegib) were approved to treat BCC and more inhibitors are in clinical investigation. However, the adverse effects and drug resistance restricted the use of Hh inhibitors. In the present study, 61 synthesized compounds containing central backbone of phthalazine or dimethylpyridazine were screened as candidates of new Hh signaling inhibitors by performing dual luciferase reporter assay. Among the compounds, L-4 exhibited an IC50 value of 2.33 nM in the Shh-Light II assay. L-4 strongly inhibited the Hh pathway in vitro and blocked the Hh pathway by antagonizing the Smoothened receptor (Smo). Remarkably, L-4 could significantly suppress the Hh pathway activity provoked by Smo mutant (D473H) which showed strong resistant properties to existing drugs such as Vismodegib. Orally administered L-4 exhibited prominent dose-dependent antitumor efficacy in vivo in Ptch+/−; p53−/− medulloblastoma allograft model. Furthermore, L-4 showed good tolerance in acute toxicity test using ICR mice. These evidences indicated that L-4 was a potent, well-tolerated, orally active inhibitor of Hedgehog pathway, and might be a promising candidate in development of Hh-targeted anti-cancer drugs.